Core Shell Investigation of 2-nitroimidazole - Bolognesi, Paola; Carravetta, Vincenzo; Sementa, Luca; Barcaro, Giovanni; Monti, Susanna; Manjari Mishra, Preeti; Cartoni, Antonella; Castrovilli, Mattea C.; Chiarinelli, Jacopo; Tosic, Sanja; Marinkovic, Bratislav P.; Richter, Robert; et al. (Frontiers in Chemistry, 2019)
Tunability and selectivity of synchrotron radiation have been used to study the excitation and ionization of 2-nitroimidazole at the C, N and O K-edges. The combination of a set of different measurements (X-ray photoelectron spectroscopy, near-edge photoabsorption spectroscopy, Resonant Auger electron spectroscopy and mass spectrometry) and computational modelling have successfully disclosed local effects due to the chemical environment on both excitation/ionization and fragmentation of the molecule.